2011
DOI: 10.1007/s12010-011-9367-z
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Characterization, and Molecular Cloning of a Novel Antifungal Lectin From the Roots of Ophioglossum pedunculosum

Abstract: A novel mannan-specific lectin was isolated from the roots of a traditional Chinese herbal medicine, Ophioglossum pedunculosum through ion-exchange chromatography and gel filtration. With a molecular mass of 19,835.7 Da demonstrated by MALDI-TOF analysis, this novel agglutinin was designated as O. pedunculosum agglutinin (OPA), specifically agglutinating human O erythrocytes and rabbit erythrocytes. The hemagglutination could be strongly inhibited by mannan and thyroglobulin, the activity of which was stable i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…Ganapati et al [23] studied the lectin of R. vivipara and demonstrated that it is stable in a pH range of 2 to 9. Lectin isolated from Ophioglossum pedunculosum maintained its HA at pH from 4-8 [34].…”
Section: Resultsmentioning
confidence: 99%
“…Ganapati et al [23] studied the lectin of R. vivipara and demonstrated that it is stable in a pH range of 2 to 9. Lectin isolated from Ophioglossum pedunculosum maintained its HA at pH from 4-8 [34].…”
Section: Resultsmentioning
confidence: 99%
“…Homoflavonoids from O. petiolatum have antihepatitis B virus activity (Lin et al 2005b;Wan et al 2013). O. pedunculosum contains 3-O-methylquercetin glucosides that inhibit lipopolysaccharideinduced NO production in macrophages (Wan et al 2012), and a mannan-specific lectin with antifungal activity (He et al 2011). An alcohol-ethyl acetate fraction from O. thermale has shown anti-inflammatory effects on carrageenan-induced inflammation, which may be related to the extract's antioxidant properties (Zhang et al 2012d).…”
Section: Ophioglossaceaementioning
confidence: 99%
“…Lectins from Phaseolus vulgaris seeds inhibited the growth of Coprinus comatus and Rhizoctonia solani [88] as well as Valsa mali [89]. A mannan-specific lectin from Ophioglossum pedunculosum roots strongly damaged the growth of Sclerotium rolfsii at 40 μ g/mL [90]. …”
Section: Antifungal and Antiparasitic Activities Of Lectinsmentioning
confidence: 99%